Effects of Chromium-L-Methionine in Combination with a Zinc Amino Acid Complex or Selenomethionine on Growth Performance, Intestinal Morphology, and Antioxidative Enzymes in Red Tilapia Oreochromis spp. - Rawiwan Limwachirakhom; Supawit Triwutanon; Srinoy Chumkam; Orapint Jintasataporn (Animals, 2022)
To consider diet optimization for the growth and health of fish under intensive aquaculture systems, with a focus on the farming of Nile tilapia and red tilapia in Thailand, we conducted an experiment based on a completely randomized design (CRD), with three treatments and four replicates. Three diets, supplemented with different trace minerals, were applied to selected groups of fish: (a) a control diet, without organic trace minerals supplementation; (b) a T1 diet of chromium-L-methionine at 500 ppb, in combination with a zinc amino acid complex at 60 parts per million (ppm); and (c) a T2 diet of chromium-L-methionine at 500 ppb in combination with selenomethionine at 300 ppb. Red tilapia with an initial mean weight of 190 ± 12 g/fish were randomly distributed into cages of 2 × 2 × 2.5 m in a freshwater pond (12 cages in total), with 34 fish per cage and a density of 17 fish/m3. During the 8 week feeding trial, the fish were fed 3–4% of their body weight twice a day. The fish were weighed, then blood samples were collected to study their immune responses. The intestines were collected, measured, and analyzed at the end of the feeding trial. The results showed that the red tilapia that were fed with diets of chromium-L-methionine in combination with a zinc amino acid complex in the T1 treatment had significantly (p < 0.05) higher final weights, weight gains, average daily gains (ADGs), and better feed conversion ratios (FCRs), compared with fish that were fed with the control diet without organic trace minerals and with fish that were fed with the T2 diet (p < 0.05). The midgut and hindgut villus heights of the group fed with chromium-L-methionine in combination with a zinc amino acid complex in the T1 treatment were significantly higher than those of the other groups (p < 0.05). The levels of the antioxidative enzyme superoxide dismutase (SOD) and lysozyme activity were not significantly different from those of fish that were fed with the control diet (p > 0.05), whereas the glutathione level tended to increase (p < 0.1) in fish that were fed with chromium-L-methionine in combination with selenomethionine in the T2 treatment. Therefore, we concluded that chromium-L-methionine in combination with a zinc amino acid complex or selenomethionine clearly enhanced red tilapia’s growth performance and feed utilization through the promotion of antioxidative enzyme activity and immune response.